Ethnocentric HRM policies in the Asia Pacific region: An explanation of Host Country resistance - Wes Harry; Chizu Nakajima (Management Revue, 2007)
This paper considers the impact of ethnocentric policies, using as an example diversity policies, created by Multinational Companies (MNCs), Non Government Organisations (NGOs) and international agencies then imposed on a host country and its population. Examples of practices in the Asian Pacific region illustrate how the experience of colonialisation, war and migration have major impact on perceptions of the Host Country governments and nationals The paper discusses possible reasons for Host Country Nationals (HCNs) to resist foreign, apparently, ethnocentric policies. The resistance is often based on the experience of being colonised or the fragile social cohesiveness by the host nations. The motives of the MNC are often perceived to be to weaken the host nation and its organisations so as to be able to dominate the local economy as part of globalisation, taking little, if any, account of local needs and sensitivities. The imposition of ethnocentric policies shows that the parent organisations are not MULTInational but SINGLEnational Companies.
Keywords: 650; Asian management; diversity; ethnocentric policies; HRM; resistence to globalization; Management; Diversity Management; Personalmanagement; Globalisierung; Asiatisch-pazifischer Raum